Comparison of Intra-Arterial Chemotherapy Efficacy Delivered Through the Ophthalmic Artery or External Carotid Artery in a Cohort of Retinoblastoma Patients - Jia, Shichong; Wen, Xuyang; Zhou, Min; He, Xiaoyu; Han, Minglei; Fan, Jiayan; Jia, Renbing; Fan, Xianqun (Frontiers in Medicine, 2021)
Purpose: To evaluate the efficacy of an external carotid artery (ECA) alternative route in intra-arterial chemotherapy (IAC) for treatment of retinoblastoma. Methods: In this retrospective, single-centre, case-control study, 98 retinoblastoma patients who received successful IAC were included. The drug delivery routes were the primary ophthalmic artery (OA) route and the ECA route when OA catheterization was not feasible. Results: A total of 337 successful IAC procedures were performed in our study, of which 32 (9.5%) procedures were performed through the ECA route. Eighteen eyes (18.4%) accepted at least one IAC through branches of the ECA. Statistical analysis showed that there was no significant difference in ocular clinical results (enucleation, death, recurrence and event-free) between the ECA and OA routes. No significant association was found between the route of drug delivery and the ocular survival time (p = 0.69). The use of ECA catheterization in at least one IAC cycle was not a predictor of enucleation (HR: 1.58; 95% CI: 0.56–4.46, p = 0.39). The increasing number of procedures through the ECA route did not increase the risk of enucleation (HR: 1.64; 95% CI: 0.42–6.39, p = 0.48). Conclusion: The ECA alternative route did not affect the efficacy of IAC in retinoblastoma. When the standard OA approach is not feasible, ECA system catheterization should be considered.